2016
DOI: 10.1016/j.atherosclerosis.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a beverage rich in (poly)phenols on established and novel risk markers for vascular disease in medically uncomplicated overweight or obese subjects: A four week randomized placebo-controlled trial

Abstract: Objective: To determine if (poly)phenols alter cardiovascular risk factors, we assessed the potential of a high (poly)phenol beverage drink, rich in hydroxycinnamates and flavonoids, to modify vascular function in middle aged, overweight or obese subjects without medical comorbidity in a randomized placebo controlled pilot study. Methods: Randomly assigned active 250ml beverages containing 361mg of (poly)phenols and 120mg of vitamin C or placebo (no polyphenol / vitamin C) were taken twice daily for 4 weeks. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…After assessing different inflammatory markers, the authors did not observe any change in the circulating levels of TNF-α, IL-6, or CRP. In addition, Mullan et al (64) found no short-term evidence (4 weeks) that consumption of a beverage with a high polyphenol content and supplementation with vitamin C provided any benefits in traditional or novel risk factors in overweight or obese subjects. Moreover, in a crossover study, Gutierrez et al (65) did not find significant changes in the lipid profile, markers of oxidative stress (oxLDL, non-esterified fatty acids, NEFAs) inflammation (CRP, adiponectin, IL-6) or hypercoagulability (PAI-1 and fibrinogen) after treatment with different doses of vitamin C for 2-weeks.…”
Section: Vitaminsmentioning
confidence: 99%
“…After assessing different inflammatory markers, the authors did not observe any change in the circulating levels of TNF-α, IL-6, or CRP. In addition, Mullan et al (64) found no short-term evidence (4 weeks) that consumption of a beverage with a high polyphenol content and supplementation with vitamin C provided any benefits in traditional or novel risk factors in overweight or obese subjects. Moreover, in a crossover study, Gutierrez et al (65) did not find significant changes in the lipid profile, markers of oxidative stress (oxLDL, non-esterified fatty acids, NEFAs) inflammation (CRP, adiponectin, IL-6) or hypercoagulability (PAI-1 and fibrinogen) after treatment with different doses of vitamin C for 2-weeks.…”
Section: Vitaminsmentioning
confidence: 99%
“…Besides, no significant differences were seen in the plasma levels of leptin, apolipoproteins, cystatin C, insulin, adiponectin, CRP, intercellular adhesion molecule 1, E -selectin, or tissue plasminogen activator, but the IL-6 level increased in active versus placebo recipients (0.32 pg/ml vs 0.18 pg/ml; P = 0.01). 39 Quercetin was reported to reduce CRP expression in mice, although this finding has not been verified in clinical trials. 40 Using the PLR for monitoring anti -inflammatory effects of a diet is a novel approach, but it is also in line with a recent systematic review by Kurtul and Ornek including 111 studies, 41 which provided evidence for the association of the PLR with CVD and its possible use as a prognostic marker of CVD.…”
mentioning
confidence: 97%
“…Thus, Soltani et al examined the effects of a Vaccinium arctostaphylosfruit extract on hyperlipidemic adult patients and even if no significant effects were observed regarding HDL and CRP, a significant reduction of total cholesterol, LDL, triglycerides and malondialdehyde (MDA) levels was obtained (Soltani et al, 2014). Furthermore, Mullan et al showed that administering a vitamin C and polyphenol-rich beverage didn't induce a reduction of metabolic or inflammatory markers (apolipoproteins, CRP, ICAM-1, E-selectin) (Mullan et al, 2016).…”
Section: Anti-inflammatory Potential Of Polyphenols In Humansmentioning
confidence: 99%